Changes in Transcript Related to Osmosis and Intracellular Ion Homeostasis in Paulownia tomentosa under Salt Stress - Fan, Guoqiang; Wang, Limin; Deng, Minjie; Zhao, Zhenli; Dong, Yanpeng; Zhang, Xiaoshen; Li, Yongsheng (Frontiers in Plant Science, 2016)
Paulownia tomentosa is an important economic and greening tree species that is cultivated widely, including salt environment. Our previous studies indicated its autotetraploid induced by colchicine showed better stress tolerance, but the underlying molecular mechanism related to ploidy and salt stress is still unclear. To investigate this issue, physiological measurements and transcriptome profiling of diploid and autotetraploid plants untreated and treated with NaCl were performed. Through the comparisons among four accessions, for one thing, we found different physiological changes between diploid and autotetraploid P. tomentosa; for another, and we detected many differentially expressed unigenes involved in salt stress response. These differentially expressed unigenes were assigned to several metabolic pathways, including “plant hormone signal transduction”, “RNA transporter”, “protein processing in endoplasmic reticulum” and “plant-pathogen interaction”, which constructed the complex regulatory network to maintain osmotic and intracellular ion homeostasis. Quantitative real-time polymerase chain reaction was used to confirm the expression patterns of 20 unigenes. The results establish the foundation for the genetic basis of salt tolerance in P. tomentosa, which in turn accelerates Paulownia breeding and expands available arable land.